TUBERCULOSIS MUSCULOESQUELÉTICA QUE IMITA NEOPLASIA DE TEJIDOS BLANDOS: A PROPÓSITO DE DOS CASOS - Jaime A. Patiño-Niño (Asociación Colombiana de Infectología, 2021)
Tuberculosis (TB) is one of the infectious diseases with the highest burden of morbidity and mortality worldwide. Pulmonary presentation is the most common, however, extrapulmonary manifestations, especially osteoarticular, can be difficult to diagnose due to their nonspecific symptoms suggestive of other entities such as neoplasms or infiltrative diseases. Tuberculosis is also associated with multiple risk factors, especially immunosuppression, and among others, household contact with patients with tuberculosis or residing in an endemic area. We present two pediatric patients without immunecompromise, with clinical history suggestive of musculoskeletal neoplasms, with congruent imaging findings, but with positive microbiological studies for TB.